Next Chapter : from mall to meeting ground - Una Mjöll Ásmundsdóttir 1996- (2024)
Over the past three decades, society has undergone significant changes impacting shopping malls worldwide. This development has resulted in a sense of loss within the community of Hafnarfjörður and left Fjörðurinn, a shopping mall, with a silent heart longing for a beat. As the face of the harbour and the main transport hub in town, I recognize the importance and potential of the building and believe it deserves to be cared for and reimagined to better serve changing needs. How can the mall be transformed, to optimize social interaction, cultural engagement, and civic participation within the local community?